Análisis de comunidades bacterianas asociado a la rizosfera del mortiño (Vaccinium floribundum) en la cooperativa Cotopilalo, parroquia Toacaso, provincia de Cotopaxi 2023. - Angamarca Colala, Morayma Coley (2023)
This research project was carried out in the Cotopilalo cooperative, Toacaso parish, Cotopaxi province, with the general objective of analyzing the communities associated with the mortiño rhizosphere (Vaccinium floribundum), in two altitudinal floors of 3928 and 3673 masl, through an analysis metagenomic and soil analysis. Specific objectives were raised such as: Identify bacterial diversity of the rhizosphere of the mortiño, group the bacterial communities by species related to the rhizosphere of the mortiño. In the study, several activities were carried out, such as: the delimitation of the study area by means of GPS (Gobal Positioning System) by which it helped us to determine the height and the X, Y coordinates of each one of the altitudinal floors, later it was taken the samples of the rhizosphere of the mortiño in the study area, we proceed to take the subsamples. For this, a zig-zag route is made on the ground, taking subsamples at each vertex, once the samples are ready, they are sent to the Bio-Sequence laboratory for their respective analysis, in the same way the determination of physical-physical properties is carried out. chemicals through a soil analysis in the Agrar-PROJEKT laboratory. With the results obtained from the two analyses, the alignment was carried out to obtain a taxonomic tree of bacterial communities identified by species in each altitudinal level and the species grouping dendrogram between soil 1 and 2. Finally, it was determined that soil 1 is the most diverse because it has not been treated by humans or animals, Canditus Solibacter being the most diverse and dominant bacterium in this altitudinal floor, taking into account that the conditions considerably influence this crop. Edaphic.